Microbiology and resistance in first episodes of spontaneous bacterial peritonitis: implications for management and prognosis - Friedrich, Kilian; Nüßle, Simone; Rehlen, Tobias; Stremmel, Wolfgang; Mischnik, Alexander; Eisenbach, Christoph (Journal of gastroenterology and hepatology, 2016)
Purpose International guidelines for antibiotic treatment of spontaneous bacterial peritonitis (SBP) are based on studies conducted decades ago and do not reflect regional differences of bacterial epidemiology. Methods We retrospectively analyzed epidemiology of agents, antibiotic resistance patterns, and survival in liver cirrhosis patients with their first episode of SBP during the years 2007-2013. Results Of the 311 patients included, 114 patients had a positive ascites culture, and 197 had an ascitic neutrophil count >250 μL. Gram-positive bacteria (47.8%) were more frequently found than Gram-negatives (44.9%), fungi in 7.2%. Enterobacter spp. (40.6%), Enterococcus spp. (26.1%), and Staphylcoccus spp. (13.8%) were the most frequently isolated agents. Third-generation cephalosporins covered 70.2% of non-nosocomial and 56.3% of nosocomial-acquired SBP cases.When SBP was diagnosed by a positive ascitic culture, survival was highly significantly reduced (mean: 13.9 ± 2.9 months; 95% confidence interval [CI]: 8.1-19.8) compared with culture-negative SBP patients (mean: 44.1 ± 5.4 months; 95% CI: 33.4-54.9; P = 0.000). Along with model of end-stage liver disease score and intensive care unit contact, a positive ascites culture remained an independent risk factor associated with poor survival (odds ratio: 1.49; 95% CI: 1.09-2.03) in multivariate analysis; piperacillin/tazobactam proved to be an adequate antibiotic for nosocomial and non-nosocomial SBP in 85.1% and 92.5%, respectively. SBP infection with Enterococcus spp. was associated with poor patient survival (P = 0.048). Conclusions Third-generation cephalosporins have poor microbial coverage for treatment of SBP. Current guidelines need to adapt for the emerging number of Gram-positive infectious agents in SBP patients.